Pharmacists and telemedicine: an innovative model fulfilling Sustainable Development Goals (SDGs) - Nadia Bukhari (BMC, 2021)
Abstract The lack of access to safe medicines and quality healthcare services in peri-urban and rural areas is a major challenge driving a health system to innovate new models of care. This commentary will discuss the implementation and impact of the “Guddi baji” tele-pharmacy model, a project piloted by doctHERs, one of Pakistan’s leading telemedicine organizations. This innovative model has described the reintegration of women into the workforce by leveraging technology to improve the level of primary health care services and contributes to safe medication practice in a remote area. Our intervention proposed the deployment of technology-enabled, female frontline health workers known as the Guddi baji (meaning The Good Sister) in a rural village. They serve as an “access point to health care” that is linked to a remotely located health care professional; a licensed doctor or a pharmacist within this model.